Beneficial partnership. - The Star, Alycia Lim (2011)
UNIVERSITI Putra Malaysia (UPM) recently signed a memorandum of understanding (MoU) with the Subang Jaya Municipal Council (MPSJ) to signify their cooperation in research, education, consultancy and services in the field of forestry.